Analysis of production costs for the prototype product made from nan golden orange in the Ban Chiang Yuan community enterprise for herbal products Bo Suak Sub-district, Mueang District, Nan Province - ปานศุภวัชร, วันวิภา; กุมาร, สมบูรณ์; กุมาร, ธิตินันท์ (RMUTL Journal of Socially Engaged Scholarship, 2024)
The objectives of this study were to: 1) study the cost of investment in products; and 2) analyze the breakeven point and return on investment of herbal compress ball and herbal steam products. This is a qualitative research gathering data through participatory observation and in-depth interviews. The data were collected from 8 Ban Chiang Yuan community enterprise chairman and enterprise members. The collected data to be considered as cost of production were direct material, direct labor and operating expense. Then, the breakeven point and return on investment were calculated. The study found that; 1) Herbal Compress Ball, cost 8,894.50 baht or 88.95 baht per unit. 2) Herbal steam, cost 13,794.50 baht or 137.95 baht per unit. The sale of Herbal Compress Ball generated 12,000 Baht, with 34.21% in gross margin, whereas 25.88% in net profit whereas per production lot. The sale of Herbal steam generated 18,000 Baht, with 28.92% in gross margin, whereas 23.36% in net profit whereas per production lot. When considering the breakeven point of Nan Golden Orange as a Prototyping Product. The study found that; 1) Herbal Compress Ball the amount of sale at breakeven point was 7.75 unit or 930 Baht. per production lot. 2) Herbal steam the amount of sale at breakeven point was 6.21 unit or 1,118 Baht. per production lot. The products that had the best gross margin and net profit margin was Massage oil and Herbal Compress Ball. Therefore, business owners can set selling prices that align with the true cost of their products and make decisions to invest in production that reaches the break-even point. Therefore, the Ban Chiang Yuen Herbal Community Enterprise can also plan to manufacture products that generate the highest possible profit. Additionally, the Ban Chiang Yuen Herbal Community Enterprise has developed a prototype product with a unique local identity derived from the "Nan Golden Orange" to support and promote Nan Golden Orange as the main agricultural product of Nan Province, reflecting the community's local identity. This local product will create a strategic competitive advantage and ensure the sustainable growth of the local product in the long term.